2009
DOI: 10.1021/je9004905
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressure Measurements of Hydroxyacetaldehyde and Hydroxyacetone in the Temperature Range (273 to 356) K

Abstract: Vapour pressures of ethylene glycol, hydroxyacetaldehyde and hydroxyacetone were measured by using a standard closed system equipped with a vacuum line, built recently in our laboratory. First, our vapour pressures measurements of ethylene glycol and their excellent agreement with the literature in the studied temperature range, i.e. (308 to 385) K, permitted us to validate our experimental set-up and procedure. The data obtained in the temperature ranges (296 to 356) K and (273 to 304) K were very satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…This could have led to potential impurities in the solid, one of which could be HAc, and possibly an overestimation of the vapor pressure. Magneron et al (2005) also reported partial pressure ranges for GA at 298 and 333 K and the value at 298 K was 20 times higher than Petitjean et al (2010). Petitjean et al (2010) suggested that this difference could be from volatile impurities.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…This could have led to potential impurities in the solid, one of which could be HAc, and possibly an overestimation of the vapor pressure. Magneron et al (2005) also reported partial pressure ranges for GA at 298 and 333 K and the value at 298 K was 20 times higher than Petitjean et al (2010). Petitjean et al (2010) suggested that this difference could be from volatile impurities.…”
Section: Resultsmentioning
confidence: 96%
“…The GA sensitivities determined using the melt vapor pressure source were a factor of 4 and a factor of 10 greater than the sensitivity of HAc at m/z 92 and m/z 187, respectively. Unlike Petitjean et al (2010), we did not purify the GA dimer using a freeze-pump-thaw cycle. This could have led to potential impurities in the solid, one of which could be HAc, and possibly an overestimation of the vapor pressure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations